Determination of factors that allow cryogenic nanoscopy with high power illumination without devitrification - Jan Huebinger; Philippe I.H. Bastiaens (PLoS ONE, 2026)
Cryogenic fluorescence nanoscopy, also known as super-resolution fluorescence light microscopy, has been demonstrated to be useful to close the resolution gap in cryogenic correlative light and electron microscopy (CLEM). Importantly, under cryogenic conditions fundamental resolution barriers that are imposed by molecular motion and photobleaching on fluorescence microscopy are circumvented. Due to combination of intrinsically higher resolution on the one hand with strong photobleaching and slower acquisition speed on the other hand, nanoscopy methods show the greatest resolution gain under cryogenic conditions. Therefore, cryogenic fluorescence nanoscopy has great potential also beyond CLEM. However, cryogenic nanoscopy is often limited by heating of the sample through strong laser irradiation. If the sample is heated above the glass transition temperature, diffusion and conformational changes perturb the sample and the sample eventually devitrifies. Reported tolerable power densities on different systems vary by several orders of magnitude. We therefore investigated the laser-induced heating in different setups for cryogenic nanoscopy by time-dependent finite-element simulations complemented with absorption measurements of mammalian cells. This showed that laser-induced heating happens in milliseconds in these setups, precluding efficient sample preservation by intermittent illuminations unless the laser power is modulated in the kHz regime. Under moderate (kW/cm 2 ) light densities used for single molecule localization microscopy, absorbance by mammalian cells was too weak to explain devitrification. Here, heating is governed by absorption of supporting material and can therefore be alleviated by optimizing this material. However, the much higher power densities used in stimulated emission depletion nanoscopy (MW/cm 2 ) resulted in temperatures clearly above the devitrification temperature from absorption by cells alone. Therefore, samples should be mounted on an efficient heat exchanger, such as a diamond, for high power illumination schemes.